PENGARUH KUALITAS SUMBER DAYA MANUSIA, KOMUNIKASI, KOMITMEN ORGANISASI, MOTIVASI KERJA, DAN KOMPENSASI TERHADAP KINERJA PEGAWAI NEGERI SIPIL DI LINGKUNGAN PEMERINTAH PROVINSI SUMATERA SELATAN - Frecilia Nanda Melvani (JURNAL KOMPETITIF, 2016)
This study aims to determine the influence of the quality of human resources, communications, organizational commitment, motivation and compensation to the performance of Civil Servants in the Environment Government of South Sumatra Province either simultaneously or partially. The method used is descriptive method with multiple regression analysis. In this study using Proportional Random Sampling as a sampling technique. Sources of data and population in this study is a Civil Servant in 4 (four) Unit of Local Governments of South Sumatra Province, among others: Regional Development Planning Board (Bappeda), the Agency for Promotion and Licensing Investment (BP3MD), SERVISE community and village authorities (BPMPD) and the Department of Trade and Industry (Industry and Trade) who have qualified education Strata 1 (S1), Strata 2 (S2), Tier 3 (S3) as many as 79 employees. Simultaneously factors Quality of Human Resources (HR), Communication, Organizational Commitment, Work Motivation and Compensation amounting to 50.0% have influence on the performance of Civil Servants in the Environment Government of South Sumatra Province.Partially Human Resources quality factors have an influence by 24.8% to employee performance, and communication factors have an impact of 23.5% on employee performance, further factors influence organizational commitment have amounted to 23.5% of the employee's performance, while the motivational factors work has amounted to 26.0% influence on employee performance, and compensation factors have an influence of 21.7% to the performance of Civil servants in the Environment Government of South Sumatra Province. Key Words: Quality of Human Resources, Communications, Organizational Commitment